Some Reflections on the Turkestan Autonomy and its Activities (Based on Archival Documents) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Based on the documents of the Fergana Regional State Archive, the article analyzes some information about the Turkestan Autonomy. In particular, documents reflecting the attitude of the local population, local government bodies and public organizations to the Turkestan Autonomy, as well as its liquidation were studied.